Electroporation-assisted discrimination of normal, benign and cancerous human gastric tissues by OCT and diffuse reflectance spectra images. (25th May 2018) - Li, Caiyun; Wei, Huajiang; Zhao, Yanping; Wu, Guoyong; Gu, Huaimin; Guo, Zhouyi; Yang, Hongqin; He, Yonghong; Xie, Shusen
Abstract: The purpose of this study is to illustrate experimentally the optical coherence tomography (OCT) signal slope and diffuse reflectance (DR) spectra of 30% and 80% glycerol combined with electroporation (EP) diffusion in normal, benign and cancerous human gastric tissues in vitro . The results of OCT showed that the permeability coefficients of 80% and 30% glycerol (both with and without EP) have the following trend: human cancerous gastric tissue  >  human benign gastric tissue  >  human normal gastric tissue under the same conditions. The permeability coefficient of the 30% glycerol group is larger than that of the 80% glycerol group under the same circumstances; the permeability coefficient of glycerol combined with the EP group is larger than that without the EP group under the same conditions. The permeability coefficient and the reduction of the DR spectra have perfect linear correlation (R 2   =  0.9745). The research results suggest that OCT and the DR spectra combined with an optical clearing agent (glycerol) and the EP method can potentially become a powerful tool for the early diagnosis and monitoring of human gastric cancer.